Experimental validation of a polyvinylidene fluoride sensing element in a tactile sensor - Yahud, S.; Dokos, S.; Morley, J. W.; Lovell, N. H. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/